Coding in Primary Grades Boosts Children’s Executive Functions - Arfé, Barbara; Vardanega, Tullio; Montuori, Chiara; Lavanga, Marta (Frontiers in Psychology, 2019)
Several programs have been developed worldwide to improve children’s executive functioning (EF). Yet, the role played in EF development by learning activities embedded in the school curriculum has received scarce attention. With two studies, we recently tested the effects of computational thinking and coding – a new element of the primary school curriculum – on the development of children’s EFs. Computational thinking (CT) stimulates the ability to define a clear and orderly sequence of simple and well-specified steps to solve a complex problem. We conjecture that CT skills are associated to such EF processes as response inhibition and planning. In a first between-group cluster-randomized controlled trial, we tested the effects of one-month coding activities on 76 first graders’ planning and response inhibition against those of one-month standard STEM activities of a control group. In a second study, we tested the effects of one-month coding activities of 17 2nd graders in two ways: within group (longitudinally), against 7 months of standard activities experienced by the same children (experimental group); and between groups, in comparison to the effects of standard STEM activities in a control group of 19 2nd graders. The results of the two studies show significant benefits of learning to code: children exposed to coding improved significantly more in planning, and inhibition tasks than control children did. The longitudinal data showed that improvements in planning and inhibition skills after one month of coding activities (8 lessons) were equivalent to or greater than the improvement attained after seven months of standard activities. These findings support the hypothesis that learning CT via coding can significantly boost children’s spontaneous development of EFs.